Intraductal carcinoma of the prostate - Szentirmai, Eszter; Giannico, Giovanna Angela (Pathologica - Journal of the Italian Society of Anatomic Pathology and Diagnostic Cytopathology, 2020)
Intraductal carcinoma of the prostate (IDC-P) is a diagnostic entity characterized by architecturally or cytologically malignant-appearing prostatic glandular epithelium confined to prostatic ducts. Despite its apparent in situ nature, this lesion is associated with aggressive prostatic adenocarcinoma and is a predictor for poor prognosis when identified on biopsy or radical prostatectomy. This review discusses diagnosis, clinical features, histogenesis, and management of IDC-P, as well as current research and controversies surrounding this entity.